Training on the Use of 'Storytelling' in Teaching Literacy - Hutami, Winanda Santi; Veronika Unun Pratiwi (Universitas Sahid Surakarta, 2024)
Good mastery of literacy today is indispensable. Especially with the state of Indonesia which is in the lower position according to the world pizza ranking. A very concerning situation where literacy is less intensified to students. According to an assessment based on the Index of Community Literacy Development (IPLM), Indonesia's score in 2022 was 64.48 on a scale of 1-100. In other conditions, the learning achievements of students at SDN Jombor 01 are generally good. But for language lessons, only a few students get good grades. The courage of students to come forward in front of the class is low because most of them are afraid of making mistakes when retelling stories using their own language. Based on these conditions, a solution is needed to improve students' literacy skills. One of them is strengthening students' literacy through storytelling. The method used in this service is storytelling. There are three media used in this literacy training, including concept maps, three part flowchart stories, and picture media. The target to be achieved from this service is an increase in knowledge about literacy through storytelling for Grade 5 students of SDN Jombor 01. In addition, this service is expected to produce several things that are achieved, including 1) teachers know more about each student's ability to understand literacy; 2) teachers can think logically and systematically by utilizing existing media in creating interesting stories through literacy training; 3) students are helped to learn to think based on point of view in thinking practices; 4) teachers can further develop students' motivation to learn; and 5) students are involved in class planning and management.